Women Managers and the Gender-Based Gap in Access to Education : Evidence from Firm-Level Data in Developing Countries - Amin, Mohammad; Islam, Asif (World Bank, Washington, DC, 2015)
Several studies explore the differences in men’s and women’s labor market participation rates and wages. Some of these differences have been linked to gender disparities in education attainment and access. The present paper contributes to this literature by analyzing the relationship between the proclivity of a firm to have a female top manager and access to education among women relative to men in the country. The paper combines the literature on women’s careers in management, which has mostly focused on developed countries, with the development literature that has emphasized the importance of access to education. Using firm-level data for 73 developing countries, the analysis finds strong evidence that countries with a higher proportion of female top managers also have higher enrollment rates for women relative to men in primary, secondary, and tertiary education.